A curious case of neuromyelitis optica spectrum disorder co-existing with idiopathic intracranial hypertension. (July 2017) - Viswanathan, S.; Wong, L.C.
Highlights: The association between neuromyelitis optica spectrum disorder and idiopathic intracranial hypertension is rare and under-recognised. The occurrence in this case is postulated to be due to dural venous sinus collapse following resolution of the swelling in the brainstem and upper cervical cord. Early recognition with sequential lumbar punctures produced early and sustained symptomatic relief.